Factors Influencing the Participation in Customers’ Loyalty Programmes: The Case of Croatia - Ivan Kovač; Dora Naletina; Dunja Brezović (Entrepreneurial Business and Economics Review)
Objective: The purpose of this research is to explore selected components of loyalty programmes in Croatia, so that retailers can conceptualise an optimal and effective loyalty programme for their customers.